Understanding Managerial Development: Integrating Developmental Assignments, Learning Orientation, and Access to Developmental Opportunities in Predicting Managerial Competencies - Dragoni, Lisa; Tesluk, Paul E.; Russell, Joyce E. A.; Oh, In-Sue (Academy of Management Journal, 2009)
Integrating the work experience, leadership development, and learning literatures, we developed and tested a model of managerial development linking experience in highly developmental assignments, a learning goal orientation, and access to developmental assignments. Based on multisource data on early-career managers, our results demonstrate that the developmental quality of managerial assignments has a positive association with end-state competencies that exceeds the association explained by tenure. Furthermore, we found that managers with stronger learning orientations, especially those with access to growth assignments, were more likely to be in developmental assignments and achieve higher levels of competence based on those experiences.